A Portrait of Pancasila Education Learning for Children with Special Needs at a Special School (SLB) Negeri 2 Mataram - Ari Hudrianto; Sunarso Sunarso; Suharno Suharno (Journal of World Science, 2024)
This study aims to determine and identify the learning of Pancasila education for children with special needs at special school 2 mataram. This research method uses a case study with a qualitative approach, data collection techniques using observation, interviews, and searches for documents and archives related to the purpose of this research. Based on the research, the subjects used were random (snowball). Based on the research subjects who came from the parties involved either directly or not in learning Pancasila Education for children with special needs at SLB 2 Mataram institution. Such as principals, students, SLB educators, and educators, especially Pancasila Education educators. To get valid data, researchers use data analysis techniques, namely data condensation, data collection, and conclusion drawing. Data triangulation techniques from both techniques and sources were obtained when researchers conducted research in the field. Therefore, the results of this study indicate that the components that make up the Pancasila Education learning tool for children with special needs are logical, structurally relevant, procedurally comprehensive, instructional, and interactive. Then, from these components to apply the Pancasila Education learning tools for children with special needs to realize inclusive education, identification, duplication, modification, adaptation, substitution, and omissions are carried out. By paying attention to several aspects such as collaboration between educators who are linear in the field of Pancasila Education in the preparation of learning tools. Then the number of educators who teach in class and the curriculum that is relevant to the needs of children with special needs.